A drug utilization and pharmacoeconomic study of anti-diabetic drugs prescribed to type 2 diabetes mellitus patients visiting the medicine out-patient department of a tertiary care hospital of north India - Singh, Amandeep; Dutta, Shakti Bala; Varma, Amit; Beg, Mirza Atif; Kumar, Hitender; Kaur, Amanjot (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Type 2 diabetes mellitus (T2DM) patients require anti-diabetic drugs on chronic basis, frequent monitoring of blood glucose levels and a number of laboratory investigations, all of which result in significant economic burden on the diabetes patients and the world economies. The purpose of this study was to analyse the prescribing pattern to highlight the current approaches to the rational use of anti-diabetic drugs in T2DM patients visiting the medicine out-patient department, and to calculate the economic burden of different anti-diabetic therapies prescribed to patients with T2DM in a tertiary care hospital of north India. Methods: This prospective study included T2DM patients visiting the out-patient department of medicine of a tertiary care hospital of Uttarakhand, India. Prescriptions of patients diagnosed as cases of T2DM were analysed as per the WHO drug use indicators. For pharmacoeconomic evaluation, the cost variation of different anti-diabetic therapies was compared using the cost-effectiveness analysis method. Results: 273 prescriptions from 148 men and 125 women were analysed. 805 drugs were prescribed to the patients with an average of 2.95 per encounter: 494 anti-diabetic drugs with an average of 1.81 drugs per patient, and 311 for co-morbid conditions. Of the 494 anti-diabetic drugs, 75.1% were oral anti-diabetic (OAD) agents and 24.9% were insulin’s. Metformin (209) and insulin aspart (42) were the most prescribed OAD and insulin, respectively. The pharmacoeconomic analysis included 138 patients. The cost per unit (1 mg/dl) reduction in fasting blood glucose was lowest with glipizide and metformin combination (INR 10.46) and highest with insulin degludec and insulin aspart combination (INR 217.38). The average total direct cost of therapy for two months was INR 2244.39 ± 2745.05 (INR 362.88 to INR 10806). 86.63% of the average total direct cost of therapy was attributed to anti-diabetic agents. Conclusions: Metformin was the most common OAD agent and insulin aspart was the most common injectable anti-diabetic drug prescribed in patients with T2DM. The newer anti-diabetic drugs sitagliptin and newer insulin analogues were also prescribed to a great extent. Overall, the prescribing trend was rational to a great extent and had improved since the earlier study in the same institute. The most cost-effective anti-diabetic therapy was combination therapy of glipizide and metformin. The cost of diabetes management is high, especially for insulin therapy.